دراسة إمكانية تعديل بعض خواص مركبات البولي استر غير المشبع بإضافة مواد مطاطية - رامي منصور; نبيل مقدسي; زبيده طه (Tishreen University, 2017)
يهدف البحث إلى دراسة إمكانية تعديل بعض خواص البولي استر غير المشبع بإضافة مواد مطاطية وذلك بهدف تحسين خصائص المرونة. استخدم لهذا الهدف نفايات إطارات السيارات بشكلين قطع وبودرة، كما استخدم أيضاً كنوع آخر المطاط السائل الستارين بوتادين. ثم تم رصد التعديل من خلال قياس قدرة المواد المركبة الناتجة على امتصاص طاقة الاهتزاز وتخفيض الضجيج الناتج عن دوران عمود كرنك لامركزي وذلك عند سرعات دوران مختلفة(300,500,700)rpm . أظهرت نتائج الاختبارات وجود تعديل في بنية المركبات عند سرعة دوران منخفضة (300 rpm) في حين أظهرت نتائج مختلفة عند سرعات الدوران العالية. This paper is targeting towards studying on the possibility to modify some properties of unsaturated Polyester compounds by adding rubber materials in order to improve its flexibility property. For this target, Waste of cars' tires was used in two forms powder and pieces, and the liquid rubber Styrene-butadiene was used as another type of rubber. After that the modification was detected by measuring the possibility of the resulted compound materials to absorb vibration power, and reduce the noise that is produced by eccentric crankshaft circulation at different rotating speeds, (300, 500, 700) rpm. Test results demonstrate that there will be Modification in the construction of the compounds at low rotating speeds (300 rpm). On the other hand, it demonstrates different results at high rotating speeds.